2(g-2)-4=2

Simple and best practice solution for 2(g-2)-4=2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(g-2)-4=2 equation:


Simplifying
2(g + -2) + -4 = 2

Reorder the terms:
2(-2 + g) + -4 = 2
(-2 * 2 + g * 2) + -4 = 2
(-4 + 2g) + -4 = 2

Reorder the terms:
-4 + -4 + 2g = 2

Combine like terms: -4 + -4 = -8
-8 + 2g = 2

Solving
-8 + 2g = 2

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add '8' to each side of the equation.
-8 + 8 + 2g = 2 + 8

Combine like terms: -8 + 8 = 0
0 + 2g = 2 + 8
2g = 2 + 8

Combine like terms: 2 + 8 = 10
2g = 10

Divide each side by '2'.
g = 5

Simplifying
g = 5

See similar equations:

| -7n-2=10 | | C=6m+3.5 | | 6789*3366=3x-4y | | x^2+x+3=6x+3 | | 2(8x+2)=-17-2x-3x | | (2x^4)-(5x^3)-(76x^2)-(96x)=0 | | N^2-7n-25=0 | | 5(b-2)=b+10 | | -(4p-4)=-29+7p | | 8r-14=22+4r | | -(4p-4)=-2+7p | | 2t-10=-10+5t | | 6(-2r+2)=12-2r | | 3x=98 | | x^2+6x+46=-6x+10 | | -13+2w=-8w+w | | 2.5m=5.30 | | 2247.995-2161.877=86.125 | | [(8m^2+2m-5)-(10m^2-5m+5)]-(m^2+m+4)= | | (y-5)/3=6 | | 7(-3x+2)=8(3y-2) | | 2x+19=3x-1 | | X-4=.5x+6 | | 7x-23=2x+47 | | (c+3)+2c=21 | | 2x^2+4x-10=4x+8 | | 17-2(x-4)=9 | | y=0.09x+2.89 | | 6d-96=10d | | -31-4=-5-5(1+5x) | | 2(3+4x)-1=21 | | 88=n+n+2(n+20) |

Equations solver categories